The Image of Guru Nanak in Dadu-Panthi Sources - Fenech, Louis (Religions, 2020)
This essay examines the issue of Guru Nanak’s inclusion in the mid-to-late seventeenth-century devotional text prepared by the Dadu-panthi savant, Raghavdas, the Bhakt-māl or Garland of Devotees. This text follows by some decades the similarly titled Bhakt-māl of Nabha Das. However, while Nabha Das excludes Guru Nanak, Raghavdas’ Bhakt-māl embraces him and includes a much more diverse seventeenth- and pre-seventeenth-century saintly clientele that was particular to both northern and southern India. The essay is one of the first to examine this text in Sikh studies and tease out the reasons which may have prompted Raghavdas to include Guru Nanak. In the process, it attempts to understand early non-Sikh bhakti views of the Sikh Gurus while also providing fresh looks at Sikh numbers in the late sixteenth and early seventeenth centuries and at the diverse and multi-ideological environment of northern India from the early 1600s onward. It also suggests Raghavadas’ familiarity with the poetry of his near contemporary ideologue, the great Sikh scholar Bhai Gurdas Bhalla.